Peran lingkungan keluarga dalam meningkatkan kesehatan mental remaja - Munawaroh, Yuni Rizky Faitul (Maliki Interdisciplinary Journal, 2024)
Mental health refers to a condition of well-being where individuals are capable of living fulfilling lives, functioning effectively, and making positive contributions to society. It includes not just the lack of mental disorders but also the capacity to regulate emotions and engage socially. The family setting is vital in influencing adolescent mental health, as conflicts within the family can lead to behavioral challenges and mental health issues in youths. This study seeks to determine the frequency of mental health problems among adolescents, the factors that influence these issues, and the ways in which the family environment can promote mental health. By recognizing the role of the family, effective strategies can be established to improve the mental well-being of young people in Indonesia.